2020
DOI: 10.3346/jkms.2020.35.e254
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Uric Acid Level and ESRD or Death in a Korean Population

Abstract: Background: Serum uric acid (SUA) is recognized as a risk factor for chronic kidney disease (CKD) and mortality. However, there is controversy as to whether a high or low level of SUA is related to the risk of CKD progression or death, and whether it differs between males and females. Methods: We included 143,762 adults who underwent voluntary health screening between 1995 and 2009 in Korea. For each sex, we divided participants into sex-specific quintiles according to SUA levels and compared end-stage renal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The relationship between SUA and mortality has been explored in previous studies. Similarly, several studies including a longitudinal Taiwanese cohort study ( 23 ), US adult cohort study ( 24 ), Korean study ( 25 , 26 ) and Chinese chronic kidney disease study ( 17 ) reported U-shaped associations between SUA and all-cause mortality as well as cardiovascular mortality. Nevertheless, the different patient populations recruited might affect the occurrence of ending events to affect different SUA cutoff values and ranges of variation.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between SUA and mortality has been explored in previous studies. Similarly, several studies including a longitudinal Taiwanese cohort study ( 23 ), US adult cohort study ( 24 ), Korean study ( 25 , 26 ) and Chinese chronic kidney disease study ( 17 ) reported U-shaped associations between SUA and all-cause mortality as well as cardiovascular mortality. Nevertheless, the different patient populations recruited might affect the occurrence of ending events to affect different SUA cutoff values and ranges of variation.…”
Section: Discussionmentioning
confidence: 94%
“…Egger’s test indicated no significant evidence of publication bias ( p = 0.421). Another 8 studies [33-40] covered HR of the minimum or maximum group as compared with the middle group. Patients exhibiting minimum or maximum level of SUA were both associated with an increased risk of all-cause mortality compared with those exhibiting middle level (HR, 1.36; 95% CI, 1.20–1.54, p < 0.00001; HR, 1.39; 95% CI, 1.05–1.83, p = 0.02).…”
Section: Resultsmentioning
confidence: 99%
“…Hyperuricemia is a strong independent risk factor for incident CKD [14][15][16][22][23][24][25][26][27][28] . The relationship of serum uric acid with incident CKD is not linear, but risk shows a rapid increase as serum uric acid concentrations reach 7 mg/dL or more 29,30 .…”
Section: Epidemiology Of the Associationmentioning
confidence: 99%